Getting Above Our Raising: A Case Study of Women from the Coalfields of Southwest Virginia and Eastern Kentucky - Mary Darcy O'Quinn (Journal of Research in Rural Education, 1999)
This study describes Appalachian women in transition, addressing the following questions: Did traditional Appalachian women establish an identity distinct from theirfamily roles? Do younger Appalachian women construct a sense of both belonging and intimacy within the family and independence from the family? Data were collected over a five-year period. Findings show that traditional women devoted their lives to the survival ofthe family. Younger miners' wives and daughters who did not attend college identify strongly with their mothers. However, they want more financial independence than their mothers experienced. Contemporary women who attend college identify strongly with theirfathers who support them in terms of their education. In higher education, however, these mountain women felt out of place and insecure, despite academic success. Findings are being used to develop an intervention program based on the notion that women in transition need resources and educational systems that empower them to develop their talents.